β-Nitrostyrenes as Potential Anti-leishmanial Agents - Shafi, Syed; Afrin, Farhat; Islamuddin, Mohammad; Chouhan, Garima; Ali, Intzar; Naaz, Faatima; Sharma, Kalicharan; Zaman, Mohammad S. (Frontiers in Microbiology, 2016)
ABSTRACT Development of new therapeutic approach to treat leishmaniasis has become a priority. In the present study, the antileishmanial effect of β–nitrostyrenes was investigated against in vitro promastigotes and amastigotes. A series of β–nitrostyrenes have been synthesized by using Henry reaction and were evaluated for their antimicrobial activities by broth microdilution assay and in vitro antileishmanial activities against Leishmania donovani promastigotes by following standard guidelines. The most active compounds were futher evaluated for their in vitro antileishmanial activities against intracellular amastigotes. Among the tested β–nitrostyrenes, compounds 7, 8, 9, 12 and 17 exhibited potential activities (MICs range, 0.25–8 µg/mL) against clinically significant human pathogenic fungi. However, the microbactericidal concentrations (MBCs) and the microfungicidal concentrations (MFCs) were found to be either similar or only 2‒fold greater than the MICs. Anti–leishmanial results demonstrated that compounds 9, 12, 14 and 18 were found to be most active among the tested samples and exhibited 50 % inhibitory concentration (IC50) by 23.40±0.71, 37.83±3.74, 40.50±1.47, 55.66±2.84 nM against L. donovani promastigotes and 30.5±3.42, 21.46±0.96, 26.43±2.71 and 61.63±8.02 nM respectively against intracellular L. donovani promastigotes amastigotes respectively which are comparable with standard AmB (19.60 ± 1.71 nM against promastigotes & 27.83±3.26 nM against amastigotes). Compounds 9, 12, 14 and 18 were found to have potent in vitro leishmanicidal activity against L. donovani and found to be non–toxic against mammalian macrophages even at a concentration of 25 µM. Nitric oxide (NO) estimation studies reveals that these compounds are moderately inducing NO levels.